PEMBUATAN DAN SOSIALISASI PENGGUNAAN ALAT BANTU CRANE TROLLY JIG AIR SPRING PADA SARANA MRT JAKARTA - Atmaja, Dadang Sanjaya; M Nurhadi; Damayanti, Ajeng Tyas; Utomo, Ilham Satrio; Rihandoyo, Ken Ken Tabitha; Fajar, Hafidh Fiqran (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
The maintenance of air springs on ND-748 and ND 748-T type bogies in Jakarta MRT facilities requires a complex and time-consuming process. This community service research project aims to design, develop, and socialize the use of a crane trolly jig air spring tool to improve the efficiency of the maintenance process. The methodology employed includes data collection, chain block calculations, design using Solidworks 2023, and a manufacturing process encompassing tool and material preparation, material cutting, welding, component assembly, and finishing. Testing results indicate that the developed tool is safe to use and functions properly. This tool can reduce the time required for air spring removal and maintenance from 4-5 minutes to a more efficient duration, while facilitating installation at a rate of 5 minutes per air spring. As part of the community service aspect, this auxiliary tool has been handed over to PT. MRT Jakarta, accompanied by socialization of its usage to facilitate maintenance of their facilities. This research is expected to contribute to improving efficiency and safety in the maintenance of public transportation systems in Jakarta.